Implementation of Duolingo Application as Learning Media to Improve Student’s Speaking Skill at SMK Pariwisata Aisyiyah Sumbar - Adinilachry, Athaariq; Hanifa, Rizaldy (Universitas Negeri Padang, 2024)
The teaching and learning process is closely related to the use of gemification. Many English teachers use gemification as a medium to help them in teaching. For teachers, the use of gemification in the teaching and learning process can make students have fun and interesting learning. For some students, gamification may be beneficial for them in learning English. Therefore, researchers want to know students' perceptions of using the Duolingo application as a speaking learning medium. This study was a Classroom Action Research. A classroom Action Research (CAR). This research was conducted at Aisyiyah Tourism Vocational School, West Sumatra. Participants, 20 students from second grade, gave positive perceptions about the Duolingo application. This research shows that most students prefer to learn to speak English using the Duolingo application as a medium. There are several advantages that can be taken from using the Duolingo application as a medium for learning to speak English, such as it is easy for them to understand the material, they are more enthusiastic and motivated in learning to speak English, Duolingo can eliminate boredom in learning and also encourage them from new ideas in learning.